Strength of the trilinear Higgs boson coupling in technicolor models - Doff, A.; Natale, A. A. (Elsevier B.V., 2006)
We discuss the strength of the trilinear Higgs boson coupling in technicolor (or composite) models in a model independent way. The coupling is determined as a function of a very general ansatz for the technicolor self-energy, and turns out to be equal or smaller than the one of the Standard Model Higgs boson depending on the dynamics of the theory. (c) 2006 Published by Elsevier B.V.
Keywords: technicolor models; Non-Standard Model Higgs bosons